Analisis Dan Perancangan Dan Implementasi Sistem Pembayaran Donasi Berbasis Payment Gateway Pada Platform Web - Mohammad Muzaky Al-Amin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to improve the efficiency of donation systems through the integration of a responsive and user-friendly web-based payment gateway. Conventional donation systems still face various challenges, such as limited payment methods, time-consuming manual verification processes, and a lack of transparency in transaction recording. By utilizing payment gateway technology, users can make donations directly through various payment methods, including bank transfers, e-wallets, and credit cards, in real time. The system is developed using a modern web development approach with a PHP framework (CodeIgniter) and a Vue.js-based frontend interface. The implementation results show that the system is able to accelerate the payment process, improve the accuracy of transaction records, and provide convenience in donation monitoring for administrators. This system integration also supports the automatic delivery of digital donation reports. In the future, the system is expected to be further developed by adding instant notification features and donation history tracking to enhance public trust and participation in digital-based social activities.